The impact of war on animal welfare: the Imperial Japanese Navy’s manipulation of pigeon behavior in WW II - Cheng Peng; Zi-qi Luo; Lin-hui Guo; Yi-fei Zhu (Humanities & Social Sciences Communications)
Abstract Throughout modern history, animals have played a significant role in human warfare. The Imperial Japanese Navy (IJN) conducted extensive efforts to modify the natural behaviors of pigeons in order to enhance their utility in military operations. To enable pigeons to support communications aboard moving warships, the IJN exposed these land-dwelling birds to maritime environments, training them to endure challenging conditions such as inclement weather, extreme temperatures, long-distance sea flights, and night-time navigation. During the latter stages of World War II, as Japan faced intensified aerial bombardments, the IJN developed concealed underground pigeon lofts. This forced pigeons to adapt to subterranean environments. These experiments, driven by wartime demands, not only distorted the pigeons’ natural behaviors but also seriously compromised their health and survival. Many pigeons died during training and experimentation, while even larger numbers perished on the battlefield. Furthermore, the prolonged shortage of specialized military personnel led to inadequate care and neglect of the pigeons, resulting in the outbreak of infectious diseases and then deaths that could have been avoided among the birds. Despite advancements in military technologies, animals continue to be exploited in modern warfare, with their welfare and survival in ignorance. Reflecting on these historical lessons, it is imperative to recognize that modern warfare ethics should extend beyond human rights to encompass the welfare and protection of animals used in military operations.